2020
DOI: 10.5194/os-16-1367-2020
|View full text |Cite
|
Sign up to set email alerts
|

Random noise attenuation of sparker seismic oceanography data with machine learning

Abstract: Abstract. Seismic oceanography (SO) acquires water column reflections using controlled source seismology and provides high lateral resolution that enables the tracking of the thermohaline structure of the oceans. Most SO studies obtain data using air guns, which can produce acoustic energy below 100 Hz bandwidth, with vertical resolution of approximately 10 m or more. For higher-frequency bands, with vertical resolution ranging from several centimeters to several meters, a smaller, low-cost seismic exploration… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 39 publications
(56 reference statements)
0
10
0
1
Order By: Relevance
“…In addition, we implement a denoising convolutional neural network (DnCNN) to suppress random noise after stacking. We use the recommended steps and parameters of 17 layers and a mini-batch size of 128 (Zhang et al, 2017;Jun et al, 2020). We train the DnCNN model for 40 epochs and the number of iterations within each epoch is 220.…”
Section: Seismic Data and Processingmentioning
confidence: 99%
“…In addition, we implement a denoising convolutional neural network (DnCNN) to suppress random noise after stacking. We use the recommended steps and parameters of 17 layers and a mini-batch size of 128 (Zhang et al, 2017;Jun et al, 2020). We train the DnCNN model for 40 epochs and the number of iterations within each epoch is 220.…”
Section: Seismic Data and Processingmentioning
confidence: 99%
“…However, those spectra could neither be fully identified as noise since their slopes were not as high as +2. Jun et al [55] showed that after applying the machine learning noise attenuated algorithm, the noise parts of the slope spectra were converted to IW and turbulence spectra. This result also supports our "spectra contamination" theory.…”
Section: Horizontal Slope Spectra From Seismic Reflectionsmentioning
confidence: 99%
“…Thus, it is implied that, in general, seismic data could be a good substitute to estimate the spatial distribution of turbulence features, with the benefit of increased spatial resolution. Dissipation estimates from the turbulent spectral regimes were limited due to noise and thus could not be validated, although this ideally side-steps assumptions of fine-scale parameterizations: future work may apply the noise attenuation algorithm suggested by [55].…”
Section: Turbulent Dissipation Rates and Heat Fluxesmentioning
confidence: 99%
“…탄성파 자료에 기록되는 잡음은 선박 소음, 해류의 흐름이나 파도, 장비 운용 등으로 인해 발생한 무작위 잡음 과 다중 반사파(multiple), 공기파(air wave), 표면파(surface wave) 등과 같은 일관성 잡음이 있다 (Ebadi, 2017;Hlebnikov et al, 2021). 탄성파 탐사를 수행하는 과정에서 잡음이 발 생하는 요인을 완전히 억제하는 것은 매우 어렵고 탐사환 경에 따라 상이하기 때문에 탄성파 자료마다 서로 다른 잡 음특성을 가지고 있다 (Kragh and Christie 2002;Nasser et al, 2016;Waage et al, 2019) (Li et al, 2018;Zhao et al, 2019;Liu et al, 2018;Jun et al, 2020)…”
Section: 서 론unclassified